To study correlation of foot length and gestational age of new born by new Ballard score - Srivastava, Anshuman; Sharma, Utkarsh; Kumar, Sumit (International Journal of Research in Medical Sciences, 2017)
Background: It is important to know an infant’s gestational age because its behaviour and anticipated problems can be predicted on this basis. It is also important for prediction of morbidity, mortality and further management. Methods: Study was done for two years.254 newborns delivered at MYH hospital and admitted in MYH and CNBC nursery were studied. Their gestational age ranged from 27 to 42 weeks. Results: Gestational age and foot length also showed a positive correlation with a correlation coefficient of 0.99. Both AGA and SGA babies showed positive correlation of gestational age with foot length with correlation coefficient of 0.99 and 0.99 respectively. Conclusions: Foot length of 73.7 mm can be used as a cut- off point for differentiating between term and preterm babies. Foot length measurements can be easily used by peripheral health workers to differentiate between term and preterm babies. They can be used at remote places by peripheral health workers.